Why We Vote : How Schools and Communities Shape Our Civic Life - Campbell, David E., 1971- (Book collections on Project MUSE., 2006)
Why do more people vote--or get involved in other civic and political activities--in some communities than in others? Why We Vote demonstrates that our communities shape our civic and political engagement, and that schools are especially significant communities for fostering strong civic norms. Much of the research on political participation has found that levels of participation are higher in diverse communities where issues important to voters are hotly contested. In this well-argued book, David Campbell finds support for this view, but also shows that homogenous communities.